Second-trimester Ultrasound and Neuropathologic Findings in Congenital Zika Virus Infection. Issue 12 (December 2018) - Ho, Cheng-Ying; Castillo, Nicolas; Encinales, Liliana; Porras, Alexandra; Mendoza, Alejandro Rico; Lynch, Rebecca; Nemirovsky, Amy; Mantus, Grace; DeBiasi, Roberta L.; Bethony, Jeffrey M.; Simon, Gary L.; Chang, Aileen Y.
Abstract : Zika virus is a mosquito-borne virus that causes congenital Zika syndrome, characterized by microcephaly and other fetal brain anomalies. This case report presents a case of Zika virus–related fetal brain anomalies including pathologic evidence of cerebral neuronal apoptosis and macrophage infiltrates and intracerebral calcification, ventriculomegaly and corpus callosum dysgenesis detected by ultrasound at 18 weeks of pregnancy.